Proposed Posture Improvement for Tile Workers Using the Reba Method - Saputra, Prasetya Ade; Ma’ruf, Farid (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2021)
Sokka Super Sid Tile SMEs (Small and Medium Enterprises) is one of the SMEs that produce roof tiles in the Godean area. This SMEs has problems regarding workers' body positions that are not ergonomic and are carried out for a long period of time (around 7-8 hours / day) and are repeated for days, resulting in bad effects that are often felt by workers when doing their work such as when bending over, back pain, cramps in muscles and decreased ability to move. This posture issue will cause pain in the joints, muscles and ligaments, and therefore will have an impact on discomfort while working. This study aims to determine body posture in the working position after improvements have been made and provide recommendations for improvements to reduce pain felt by the workers by proposing an ergonomic work tool design. The Rapid Entire Body Assessment (REBA) method is used to determine the risk of injury to the posture of workers at each work station. Data were collected through observation, interviews and taking photo documentation at each work station. Prior to the improvement, activities that have a risk level of 2 are at the work stations of refining, pressing, and drying. Risk level 3 is at the milling, burning, and mixing work stations. Risk level 4 is at the sun-drying work station. Improvements given to the UKM are desk facilities to make their work easier and to reduce the risk of injury to workers' bodies. After improvements are implemented, the results obtained show risk level 1 is at the work station of milling, drying, refining, and burning. Risk level 2 is at the mixing, pressing and sun-drying work stations. It is concluded that the improvement of body posture in drying workers is in accordance with the ideal work posture.